Partakers in Christ (Hebrews 3.14) - Nardoni, Enrique (New Testament studies, 1991)
The translation of Heb 3.14 has been a matter of dispute. The problem lies in the ambiguity of the Greek μἐτοχοι τον χριστον. Some, like Spicq, render the clause ‘we are partners with Christ’ in the sense of companionship. The meaning would be like that of τοὺς μἐόχους σου (‘your companions’) in 1.9. Others, such as Westcott, prefer ‘partakers of Christ’ in the sense of ‘having part in him’ as in the ἔπepsilon;ις μἐρôς μἐ’ ὲμον of John 13.8. Finally others, such as O. Michel, see in it an inclusive sense encompassing both companionship with and participation in Christ.